The Simplified Carbapenem Inactivation Method (sCIM) for Simple and Accurate Detection of Carbapenemase-Producing Gram-Negative Bacilli - Jing, Xiaopeng; Zhou, Huan; Min, Xiaochun; Zhang, Xing; Yang, Qing; Du, Shuaixian; Li, Yirong; Yu, Fangyou; Jia, Min; Zhan, Yu; Zeng, Yi; Yang, Bo; et al. (Frontiers in Microbiology, 2018)
This study reports the simplified carbapenem inactivation method (sCIM) to detect carbapenemase-producing gram-negative bacilli in a simple and accurate manner. This method is based on the modified carbapenem inactivation method (mCIM) with the improvement of experimental procedures. Instead of incubating the antibiotic disk in the organism culture media, the organism to be tested was smeared directly onto the antibiotic disk in the sCIM. For evaluating the sensitivity and specificity of the method, a total of 196 Enterobacteriaceae, 73 Acinetobacter baumannii, and 158 Pseudomonas aeruginosa isolates were collected. Polymerase chain reaction (PCR) was used to detect the carbapenemase genes. Phenotypic evaluations were performed using both the sCIM and the mCIM. PCR results showed that, of the 196 Enterobacteriaceae strains, 147 expressed the carbapenemase genes blaKPC−2 (58.5%), blaIMP−4 (21.8%), blaIMP−2 (2.0%), blaVIM−1 (6.1%), blaNDM−1 (10.2%), and blaOXA−48 (1.4%). sCIM results had high concordance with PCR results (99.5%) and mCIM results (100%) with the exception of one Klebsiella pneumoniae strain, which had an minimal inhibitory concentration (MIC) for imipenem of 0.25 mg/L. PCR demonstrated that 53 of the 73 A. baumannii isolates expressed the carbapenemase genes blaOXA−23 (98.1%) and blaVIM−2 (1.8%). sCIM and PCR results corresponded but all A. baumannii isolates were carbapenemase negative by the mCIM. PCR demonstrated that 25 of the 158 P. aeruginosa isolates expressed carbapenemase genes blaVIM−1 (52%), blaVIM−2 (8%), blaVIM−4 (36%), and blaIMP−4 (4%). sCIM results had high concordance with PCR results (100%) and the mCIM results (99.4%) with the exception of one P. aeruginosa isolate that expressed the blaVIM−4 gene. The sCIM offers specificity and sensitivity comparable to PCR but has the advantage of being more user-friendly. This method is suitable for routine use in most clinical microbiology laboratories for the detection of carbapenemase-producing gram-negative bacilli.